Bilayer silk fibroin/sodium alginate scaffold promotes vascularization and advances inflammation stage in full-thickness wound. (1st July 2022) - Shen, Ying; Wang, Xinyu; Wang, Yiyu; Guo, Xiaodong; Yu, Keda; Dong, Kuo; Guo, Yajin; Cai, Cuiling; Li, Binbin
Abstract: An ideal wound dressing for full-thickness wound regeneration should offer desirable biocompatibility, adequate mechanical properties, barrier function, and cellular regulation. Here, a bilayer scaffold resembling the hierarchical structure of human skin was developed using silk fibroin and sodium alginate. The upper membrane was prepared through casting and functioned as the epidermis, whereas the lower porous scaffold was prepared by freeze-drying and mimicked extracellular matrix structures. The membrane had nonporous structure, desirable mechanical properties, moderate hydrophilic surface, and suitable water vapor transmission rate, whereas the porous scaffold revealed 157.61 ± 41.67 µ m pore size, 86.10 ± 3.60% porosity, and capability of stimulating fibroblast proliferation. The combination of the two structures reinforced the tensile strength by five-fold and provided protection from wound dehydration. A suitable degradation rate reduced potential administration frequency. Furthermore, an in vivo rabbit full-thickness wound healing test demonstrated that the bilayer scaffold facilitated wound closure, granulation tissue formation, re-epithelialization and skin component transition towards normal skin by providing a moist wound environment, advancing the inflammation stage, and stimulating angiogenesis. Collectively, as an off-the-shelf and cell-free wound dressing with single topical administration, the bilayer scaffold is a promising wound dressing for full-thickness wound regeneration.